If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -1(3x + -4) = 1 + 9 Reorder the terms: 3 + -1(-4 + 3x) = 1 + 9 3 + (-4 * -1 + 3x * -1) = 1 + 9 3 + (4 + -3x) = 1 + 9 Combine like terms: 3 + 4 = 7 7 + -3x = 1 + 9 Combine like terms: 1 + 9 = 10 7 + -3x = 10 Solving 7 + -3x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -3x = 10 + -7 Combine like terms: 7 + -7 = 0 0 + -3x = 10 + -7 -3x = 10 + -7 Combine like terms: 10 + -7 = 3 -3x = 3 Divide each side by '-3'. x = -1 Simplifying x = -1
| 5x=20-2x | | 6-2v=14 | | x+0(2)=7 | | 1x^2+15x+56=0 | | m^-2n^-5/(m^4n^3)^-1 | | -7+6p+5-2p=10 | | 2-(-9k-28)=6-15k | | 2+0y=7 | | 2-(-k-28)=6-15k | | [5-8]= | | 14x+5(5-2x)=20 | | 1.26x+3.58=1.74x+6.46 | | 3.25/5.4 | | 2(5x+1)=2(a+1) | | -3x^2+36x-108=0 | | 30/-15 | | 4x/-5x | | 9x=15x | | -5(2-2x)=2(x-3)+4 | | 4n+4=26 | | 2.1x+1.15y=2.30 | | 500=200+1.75 | | 24p^2-16p=0 | | 8-18x^2=0 | | 1x^2-16=0 | | -3(1-3b)-12=12 | | 5x+3+2x-4= | | -8x-17=3x-105 | | e=5n+8 | | 5x^2+8=4x^2-6x | | 25=-16t^2+35t+5 | | 8x^2=980 |